Value of 18F-FDG PET/CT imaging in the staging, restaging, monitoring of response to therapy and surveillance of uterine leiomyosarcomas. Issue 7 (July 2018) - Bélissant, Ophélie; Champion, Laurence; Thevenet, Hind; Weinmann, Pierre; Alberini, Jean-Louis
Abstract : Objective: Leiomyosarcoma (LMS) is the most common subtype of uterine sarcomas. It is a rare and aggressive tumour. The aim of the present study was to assess the performance of fluorine-18-fluorodeoxyglucose ( 18 F-FDG) PET/CT imaging in four clinical settings: initial staging, restaging, monitoring of response to therapy and post-therapy surveillance of uterine LMS. Patients and methods: A bicentric retrospective study was carried out on a group of 21 patients with uterine LMS for whom a total of 52 PET/CT scans were available in initial staging ( n =11), restaging ( n =11), monitoring of response to therapy ( n =17) and post-therapy surveillance ( n =13). Clinical (minimum 6 months after PET/CT scan) and/or imaging follow-up and pathology were used as the reference standard. Results: In the initial staging, the sensitivity, specificity and accuracy of PET imaging were 80, 100 and 91%, respectively. In the restaging and monitoring of response to therapy, all these indices were 100%, whereas they were lower in post-therapy surveillance at 75, 100 and 85%, respectively, because of two false-negative results. False-negative lesions were an infracentimetric lung nodule in the initial staging and a peritoneal nodule that had increased in size between two PET/CT scans in post-therapy surveillance. PET-negative lesions were all identified on the computed tomography (CT) part of the PET/CT; thus, the performances of the exam improved to 100% on taking into account the CT component of the PET/CT. Conclusion: PET/CT imaging has a high diagnostic yield in the initial staging and restaging of uterine LMS, but seems less sensitive in post-therapy surveillance. Evaluation of the CT part improves the sensitivity of the PET scan. Thus, PET/CT imaging should be considered in patients presenting with LMS.